2005
DOI: 10.1002/jcp.20334
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell exocytosis can be triggered by ammonium chloride with just a cytosolic alkalinization and no calcium increase

Abstract: A human mast cell line (HMC-1) has been used to study the effect of cytosolic alkaline pH in exocytosis. Compound 48/80, concanavalin A, and thapsigargin do not induce histamine release in HMC-1 cells. Although thapsigargin does not activate histamine release, it does show a large increase in cytosolic Ca(2+), and no change in cytosolic pH. However, when HMC-1 cells were activated with ionomycin, a significant histamine release takes place, and this effect is higher in the presence of thapsigargin. Both drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 59 publications
6
31
0
Order By: Relevance
“…We have previously described that alkalinisation induces histamine release in HMC‐1 560 in a dose‐dependent manner [Pernas‐Sueiras et al, 2005]. We showed that intracellular pH increases after NH 4 Cl addition without changing cytosolic Ca 2+ concentrations.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…We have previously described that alkalinisation induces histamine release in HMC‐1 560 in a dose‐dependent manner [Pernas‐Sueiras et al, 2005]. We showed that intracellular pH increases after NH 4 Cl addition without changing cytosolic Ca 2+ concentrations.…”
Section: Resultssupporting
confidence: 51%
“…Studies in HMC‐1 have clearly demonstrated that they also show this behaviour after alkalinisation. Exocytotic process takes place without affecting intracellular Ca 2+ concentrations [Pernas‐Sueiras et al, 2005, 2006a,b]. In those studies, we used HMC‐1 560 cells that carry a mutation in the proto‐oncogene c‐kit that leads to a Glycin → Valin amino acid exchange in position 560 of the receptor TyrK KIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionomycin depleted the stores by do permeable the endoplasmic membrane whereas thapsigargin inhibits the endoplasmic Ca 2þ -ATPase preventing stores refilling. Effect of these compounds was performed with successive addition of thapsigargin and ionomycin, that interact with thapsigargin sensitive and insensitive intracellular Ca 2þ stores [Pernas-Sueiras et al, 2005], in good agreement with findings in other cellular models [Soboloff and Berger, 2002;Turner et al, 2003]. The fact that rottlerin has effect on ionomycin and not on thapsigargininduced Ca 2þ entry could be explained in three ways, because they operate in different stores, because the store depletion activates different channels, or if the activation route is not the same.…”
Section: Discussionmentioning
confidence: 86%
“…In previous works it has been reported that in HMC-1 560 cells, the NH 4 Cl-induced intracellular alkalinization is the main stimulus to histamine release and the activation is not accompanied by intracellular calcium changes [Pernas-Sueiras et al, 2005]. HMC-1 cells are a suitable model to study intracellular calcium signaling without inducing degranulation or exocytosis processes that can affect cell viability.…”
mentioning
confidence: 99%